Corporate investment inefficiency of Chinese firms: The roles of government subsidies, political connections and ESG performance - Wang, Xiaoqian (2024)
This study aims to investigate the impact of government subsidies and political connections on corporate investment inefficiency in overinvestment and underinvestment scenarios, as well as the moderating role of ESG performance on the relationship between government subsidies, political connections and investment inefficiency in China, using an unbalanced panel dataset of 29,596 firm-year observation of Chinese listed firms for the period 2011-2021.